The Global Solutions of a Nonlinear System of Equations of Changing Type (Journal of Partial Differential Equations, 2020)
In this paper, the global existence of regular solutions to the initial-boundary value problem for a higher-order multidimensional system of equations of changing type with a strong nonlinear term is studied.
Keywords: Equations of changing type; multidimensional system; global existence; fixed point principle